2021
DOI: 10.1108/lht-06-2021-0180
|View full text |Cite
|
Sign up to set email alerts
|

Exploring individuals’ adoption of COVID-19 contact-tracing apps: a mixed-methods approach

Abstract: PurposeDuring the challenging time of lockdown and isolation due to the coronavirus disease (COVID-19), contact-tracing apps have played a critical role in health communication and preventive healthcare. This study proposed and tested an extended technology acceptance model (TAM) with key health factors (i.e. health risk perception from COVID-19, health information orientation to COVID-19 and health consciousness) to understand individuals' adoption of COVID-19 contact-tracing apps.Design/methodology/approachA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 70 publications
2
23
0
Order By: Relevance
“…Second, environmental risks do not directly affect public health code usage satisfaction, but have an indirect effect through the mediation of perceived quality. This is generally consistent with the findings of foreign studies on risk perception and digital tracking software ( 39 , 40 ). The direct effect of environmental risk on satisfaction with health code use is not significant.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…Second, environmental risks do not directly affect public health code usage satisfaction, but have an indirect effect through the mediation of perceived quality. This is generally consistent with the findings of foreign studies on risk perception and digital tracking software ( 39 , 40 ). The direct effect of environmental risk on satisfaction with health code use is not significant.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…The information system literature about the technology adoption model primarily predicts behavioral intention, usage intention, or adoption intention as the dependent variable. Most of the studies investigate this variable predictive power through PLS-SEM ( 10 , 34 , 39 ) or CB-SEM ( 35 37 , 41 ). One of the primary criteria used to examine the model's predictive capacity is the coefficient of determination ( R 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Duan and Deng ( 37 ) employed CB-SEM with an artificial neural network (ANN) approach to investigate the CTA adoption through the lens of the unified theory of acceptance and use of technology and privacy calculus theory in Australia. In contrast, the study by Nguyen et al ( 39 ) investigated the extended technology adoption model through PLS-SEM and fuzzy set/qualitative comparative analysis (fsQCA). The summary of the review findings is presented in Table 1 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The pandemic provides opportunities for advancing contact tracing and telemedicine technology. Nguyen et al (2022) explored the adoption of contact tracing apps in the US through partial least squares structural equation modelling (PLS-SEM) and fuzzy set/ qualitative comparative analysis (fsQCA). They showed that health risk perception, health information orientation and perceived usefulness of the contact tracing apps positively affected users' adoption and actual use of these apps.…”
Section: Use Of Contact Tracing Apps and Telemedicine During The Pand...mentioning
confidence: 99%